Réponses

Meilleure réponse !
2014-09-10T23:28:03+02:00
A(x)  = -3 (x + 1)(x - 2)
A(x) = -3 (x² - 2x + x - 2)
A(x) = -3 (x² - x - 2)
A(x) = -3x² + 3x + 6

B(x) = 2 (x +1)² -5
B(x) = 2 (x² + 2x + 1) - 5 
B(x) = 2x² + 4x + 2 - 5 
B(x) = 2x² + 4x - 3

C(x) = 
3 [(x-1)²+2]
C(x) = 3 (x² - 2x + 1 + 2)
C(x) = 3 (x² - 2x + 3)
C(x) = 3x² - 6x + 9
2014-09-11T00:04:36+02:00
Bonsoir

A(x)  = -3(x + 1)(x - 2)
         = -3(x² - 2x + x - 2)
         = -3(x² - x - 2)
         = -3x² + 3x + 6


B(x) = 2(x +1)² -5
        = 2(x² + 2x + 1) - 5 
        = 2x² + 4x + 2 - 5 
        = 2x² + 4x - 3


C(x) = 
3[(x-1)²+2]
        = 3(x² - 2x + 1 + 2)
        = 3(x² - 2x + 3)
        = 3x² - 6x + 9